REALIA AS A CULTURALLY, HISTORICALLY AND TEXTUALLY DYNAMIC CATEGORY, HOW TO USE IT IN THE CLASSROOM - Saydalieva Aziza Ergashevna (American Journals Publishing, 2023)
The article considers about realia as a culturally, historically and textually dynamic category. How to use it in the classroom. There are suggested some ways of involving realias in classroom
Keywords: realia, lexical equivalents, culture specificity, static character, culture-induced problems, specific lexis.